Penggunaan Organizational Culture Assesment Instrument pada Organisasi Non Formal - Idris, Ahmad (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
The purpose of this study is to know the perceptions of the members of the community over the current organizational culture and expectations of the organizational culture members of the next 3 years. The research was conducted at Paguyuban Kios Selomangleng Kelurahan Sukorame, Kecamatan Mojoroto, Kota Kediri. This research used qualitative method with human instrument and participant observation data collection technique, and implemented organizational culture assessment instrument (OCAI) method. The results showed that the perception of members of Paguyuban Kios Selomangleng is currently in an adhocracy situation that is an organizational culture that demands innovation and initiative that can improve entrepreneurship and creativity. The hope of members of the community for the next 3 years is a market culture that is a condition where members want a competitive market culture to increase productivity and profit.